Ցուցակ Լիսաբոնի Կիւլպէնկեան թանգարանի հայերէն ձեռագրերի - Գրիգորեան, Հերմինէ (Մատենադարան)
For the first time, this work presents a complete description and the colophons of four Armenian manuscripts kept in the Gulbenkian Museum of Lisbon. These illuminated manuscripts, a Bible (Inv. no: LA 152) and three Gospel Books (Inv. no: LA 193, LA 216, LA 253), are dated to the 17th century and represent an original map of the Armenian scriptoria of Early Modern period: New Julfa, Constantinople and Crimea. The extensive colophon of LA 152 tells the story of the creation of this manuscript and provides information about individuals and events connected with it. The colophons of LA 193 and LA 216, albeit brief, mention the scribes, artists and some more details concerning these manuscripts. In LA 253, a single later note only indicates its subsequent owner. There is no main colophon in the manuscript. This small but important collection preserved in Western Europe is studied for the first time by an interdisciplinary approach, including art-historical and material study, which will enable to develop appropriate conservation and restoration procedures for the preservation of this precious cultural heritage. The appendix gives a description of another Armenian manuscript (COD. 7970) preserved in Lisbon but not included in this study. Hopefully, in the future it will be possible to refer to it in more detail. В статье впервые представлены все колофоны четырех армянских рукописей, хранящихся в Музее Гюльбенкяна в Лиссабоне. Эти иллюстрированные рукописи, Библия (Инв. но.: LA 152) и три Евангелия (Инв. но.: LA 193, LA 216, LA 253), датированы семнадцатым веком и представляют собой своеобразную карту армянских скрипториев Раннего Нового периода: Новая Джульфа, Константинополь и Крым. Обширный колофон LA 152 раскрывает историю создания этой рукописи и дает подробные сведения о лицах и событиях, связанных с ней. LA 193 и LA 216, хотя и с краткими колофонами, позволяют узнать о писцах, миниатюристах и других деталях. LA 253 указывает его последующего владельца лишь в поздней записи, а основной колофон не сохранился. Эта небольшая, но важная коллекция, сохранившаяся в Западной Европе, впервые изучается на стыке двух дисциплин – истории искусств и материального описания. Такой целостный подход поможет всесторонне представить рукописи и позволит разработать соответствующие протоколы консервации и реставрации для сохранения этого ценного культурного наследия. В приложении представлено описание еще одной армянской рукописи (COD. 7970), хранящейся в Лиссабоне, но не включенной в настоящее исследование. Мы надеемся, что в будущем можно будет обратиться к нему более подробно.
Keywords: Մատենագիտություն